(Statutory) Law - Laporta, Francisco J. (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
This paper presents a basic and general overview of the concept of law. In this sense, it warns of the risks involved in a historical approach to its concept and focuses on the study of its contemporary manifestation. Along these lines, he sets out the normative and descriptive aspects of the law as a source of law around the ideas of constitutive rules of authorities, competences and procedures. On this basis, he stipulates a definition of law and points out its characteristic forms.